Мобильный комплекс термокаталитического обезвреживания отходов - Ведь, Валерий Евгеньевич; Ровенский, А. И. (Academia de Stiinte a Moldovei, 2012)
Описана конструкция и назначение основных узлов мобильного мусороперерабатывающего комплекса типа МПК. Представлены экспериментальные данные по каталитической очистке выпускных газов. Определено, что концентрации вредных соединений в отходящих газах МПК являются значительно меньшими, нежели допускаемые нормативными документами к выбросам в атмосферу.

The design and purpose of the basic units of the developed mobile waste processing complex were described. The experimental data of catalytic purification of exhaust gases were presented. Experimental data on catalytic clearing of final gases of a designed mobile incinerator plant are shown. It is defined, that concentratings of parasitic bridgings in waste gases from setting are considerably smaller, rather than supposed by normative documents to venting.
Mobile complex catalytic thermal waste treatment
Keywords: отходы бытовые; отходы твердые; переработка; мусор; катализ; газы отработанные; municipal solid waste; waste processing complexes; catalysis; exhaust gas